A MINIMAL ROLE FOR MINIMUM TAXES - Sheffrin, Steven (Columbia Journal of Tax Law, 2020)
The 2017 Tax Cuts and Jobs Act eliminated the alternative minimum tax for corporations and sharply eviscerated the alternative minimum tax for individuals. Yet recently there has been a resurgence of interest in minimum taxes both for the international tax systems and in certain domestic contexts. This Article argues that there should be a role, but a very minimal one, for minimum taxes in our tax system. While reasonable arguments have been put forward for minimum taxes, on closer examination, many of these arguments are found wanting. This Article, however, does make a second-best case for one type of minimum tax, namely as a backstop for a potentially flawed or deficient tax. That is the “minimal role for a minimum tax.” To develop this argument, I explore three distinct theoretical rationales for minimum taxes that have been put forward. First, I discuss the distinction between unilateral and multilateral minimum taxes and the potential role that multilateral minimum taxes can play in alleviating concerns that arise from tax competition and the presence of tax havens. While unilateral minimum taxes may have a strong rationale, the rationale for multilateral minimum taxes is not compelling. Second, I show how considerations of fairness, public perception, and alternative views of the corporation create a demand for minimum taxes. This demand, however, can be satisfied in other ways. Finally, I discuss how the imperfect targeting of tax preferences and practical limitations in the design and effectiveness of the most common taxes can provide a potential, but limited, efficiency rationale for the use of minimum taxes. I lastly provide an example of the use of minimum taxes for reforming state corporate taxation.